2020
DOI: 10.1088/0256-307x/37/4/047103
|View full text |Cite
|
Sign up to set email alerts
|

Metal to Orthogonal Metal Transition*

Abstract: Orthogonal metal is a new quantum metallic state that conducts electricity but acquires no Fermi surface (FS) or quasiparticles, and hence orthogonal to the established paradigm of Landau’s Fermi-liquid (FL). Such a state may hold the key of understanding the perplexing experimental observations of quantum metals that are beyond FL, i.e., dubbed non-Fermi-liquid (nFL), ranging from the Cu- and Fe-based oxides, heavy fermion compounds to the recently discovered twisted graphene heterostructures. However, to ful… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

6
2

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…The development of quantum Monte Carlo (QMC) algorithms for a class of models of this type has created a feasible way to study this physics in an unbiased manner [14][15][16] . In QMC models, FS fermions couple to bosonic fluctuations, representing certain collective modes of low-energy fermions [17][18][19][20][21][22][23]. The bosonic part is bestowed with independent (non-fermionic) dynamics and can be tuned to criticality to mimic the situation in real materials.…”
Section: Introductionmentioning
confidence: 99%
“…The development of quantum Monte Carlo (QMC) algorithms for a class of models of this type has created a feasible way to study this physics in an unbiased manner [14][15][16] . In QMC models, FS fermions couple to bosonic fluctuations, representing certain collective modes of low-energy fermions [17][18][19][20][21][22][23]. The bosonic part is bestowed with independent (non-fermionic) dynamics and can be tuned to criticality to mimic the situation in real materials.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it has been found that designer models of fermion-boson models offer a pathway to access fermionic QCPs while avoiding the notorious sign problem in large-scale quantum Monte Carlo (QMC) simulations. Such models have been implemented in several simulations, studying nematic 49,50 , ferromagnetic 51 , antiferromagnetic [52][53][54][55][56] , gauge field [57][58][59][60][61][62] , and Yukawa-SYK-type 41 QCPs. The focusing on a particular soft boson offers an unbiased numerical test for either a Q = 0 or a finite Q analytical theory of metallic quantum criticality.…”
Section: Introductionmentioning
confidence: 99%
“…To test the efficiency of the Qiu Ku algorithm on systems with topological order, we start with a toy model of Z 2 topological phase on 2d checkerboard lattice [42][43][44], with the following Hamiltonian,…”
Section: Toy Modelmentioning
confidence: 99%